Práticas Efetivas em Educação Matemática no contexto de um banco comunitário - Meneghetti, Renata Cristina Geromel [UNESP]; De Cássia Zacheo Barrofaldi, Rita (FapUNIFESP (SciELO), 2015)
This paper is part of a project that focuses on the Mathematical Education in the context of Solidarity Economy and takes a Community Bank (CB) as a case study. It aims at the teaching and development of Mathematical activities in a contextualized way, so that the specific demands for the implementation of Enterprises in Solidarity Economy can be met, as well as the creation of some subsidies for the development of such activities. The research followed a qualitative approach (case study) and the data were collected through participant observations and semi-structured interviews. The results show Mathematics is very important to the financial management and logistics of the CB and the educational interventions made assisted the group in the organization to understand the activities of the CB and also contributed to the self-management of this Undertaking Solidarity Economy (EES).
Effective practices in mathematical education in the context of a community bank
Keywords: Ethnomathematics; Mathematics Education; Self management; Solidarity Economy; Youth and Adult Education